2013
DOI: 10.1021/ja402061q
|View full text |Cite
|
Sign up to set email alerts
|

An FeF3·0.5H2O Polytype: A Microporous Framework Compound with Intersecting Tunnels for Li and Na Batteries

Abstract: To improve the energy/power density of energy storage materials, numerous efforts have focused on the exploration of new structure prototypes, in particular metal-organic fameworks, Prussian blue analogues, open-framework oxides, and polyanion salts. Here we report a novel pyrochlore phase that appears to be useful as a high-capacity cathode for Li and Na batteries. It is an iron fluoride polymorph characterized by an intersecting tunnel structure, providing the space for accommodation and transport of Li and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
153
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(161 citation statements)
references
References 34 publications
4
153
1
3
Order By: Relevance
“…This is consistent with the result from XRD. Previous studies on the electrochemical reaction of FeF 3 with sodium had suggested that the initial discharge capacity of the FeF 3 electrode is more than 130 mAh/g when the cell was cycled between 1.5 and 4.0 V [3,4]. However, the first discharge capacity is less than 50 mAh/g for the composite electrode consisting of FeF 3 and GNS without CF x (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…This is consistent with the result from XRD. Previous studies on the electrochemical reaction of FeF 3 with sodium had suggested that the initial discharge capacity of the FeF 3 electrode is more than 130 mAh/g when the cell was cycled between 1.5 and 4.0 V [3,4]. However, the first discharge capacity is less than 50 mAh/g for the composite electrode consisting of FeF 3 and GNS without CF x (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Notably, FeF 3 sodium capacity of 250 mAh/g over a voltage range of 0. .0 V [3,4]. Recently, we have firstly indicated the reversibility of the CF x as a cathode material for SIBs and a highly reversible capacity of 1061 mAh/g with the discharge voltage plateau at 2.4 V [5], which is much higher than that of any other advanced Na storage materials reported previously.…”
Section: Introductionmentioning
confidence: 84%
“…8 There are recent reports available on a number of new materials such as layered transition metal oxides P2-Na x CoO 2 , 9 Na x [Fe 1/2 Mn 1/2 ]O 2 , 10 cubic Na x MnFe(CN) 6 , 11 NASICONtype Na 3 V 2 (PO 4 ) 3 , 12 and fluoride-based ReO 3 -type FeF 3 . 13 These pioneering work in NIBs opened a new window, albeit the fact that the reported capacities are still very low (less than 200 mAh/g) compared to LIBs.…”
mentioning
confidence: 99%
“…The MWCNTs are dispersed into the ionic liquid mixture of bmimFeCl 4 and bmimCl via "cation-p" interaction between the imidazolium cations and the p-electrons of the MWCNTs surface, resulting in the formation of a Bucky-gel. 30,31 The composition of the as-obtained material was identied by Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). 28,29 Equilibrium between FeCl 4 À and Fe 3+ , allows the precipitation of FePO 4 from the mixture, where the nano-grains are well separated due to the interfacial tension.…”
Section: Resultsmentioning
confidence: 99%